The kinds and classes of cereal grains grown in the U. S. and methods of marketing same with special reference to grading commercially - Cron, A. B. (My University, 1908)
Introduction: A cereal is any true grass that is grown for its edible seeds. There are six leading cereals in the United States which are given in the order of the area grown of each, as follows: Maize, Wheat, Oats, Barley, Rye and Rice. Buckwheat and kafir corn are sometimes called cereals.
Citation: Cron, A. B. The kinds and classes of cereal grains grown in the U. S. and methods of marketing same with special reference to grading commercially. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Grain; Cereal; Agriculture; Graduating theses; Senior theses; Theses